Consumers’ Behaviour towards Sustainable Packaging: A Study among the Students and Alumni of Faculty of Food Science and Nutrition Universiti Malaysia Sabah - Mansoor Abdul Hamid; Keneswary Ravichanthiran; Oslida Martony (Universitas Negeri Malang, 2022)
This study aims to identify the consumers’ behavior toward sustainable packaging. This study involved 284 students and alumni of the Faculty of Food Science and Nutrition, Universiti Malaysia Sabah. A questionnaire was used to garner the data, covering the participants’ demographic, consumers’ behavior, and meal preferences, as well as their knowledge of the benefit of sustainable packaging and the danger of migration of chemical substances into food from the food packaging. The obtained data were subjected to descriptive analysis. It is found that most of the respondents (71.5 percent) were aware of the benefits of sustainable packaging and the risk of migration of chemical products into food. However, the purchase of sustainably packaged products was only 43.3 percent. The education level and income of the respondents have significantly affected their purchasing behaviour. However, the family size of the respondents does not affect their purchasing behaviour. The low purchase of sustainably packaged products may be caused by numerous factors such as higher cost of sustainably packaged products, lack of information, availability, and awareness of sustainably packaged products.